Low-temperature wind tunnel model surface filling material and preparation method thereof

By using the surface filling material of the low-temperature wind tunnel model based on 196 unsaturated polyester resin, the problem of poor performance of existing putty in low-temperature environments is solved, and the surface is flat, easy to remove and does not damage the model is achieved. It is suitable for a wide range of low-temperature wind tunnel test conditions.

CN119552488APending Publication Date: 2025-03-04INST OF HIGH SPEED AERODYNAMICS OF CHINA AERODYNAMICS RES & DEV CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411807006.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the existing low-temperature wind tunnel tests, ordinary putty has poor performance at low temperatures and is prone to cracks, bubbles and even shedding. In addition, the existing T8 atomic gray putty removal is difficult and easy to damage.

Method used

The surface filling material of the low-temperature wind tunnel model including 196 unsaturated polyester resin, carbon fiber powder, glass fiber powder, accelerator and curing agent is uniformly prepared by room temperature stirring and mixing to form a filling material suitable for low-temperature environment.

Benefits of technology

The filling material has a flat surface and no cracks. It has a wide range of application. It has stable performance at high/low temperatures, reduced hardness, easy to remove, and does not damage the model. It is suitable for conditions such as 0.15≤M≤4.0, 77K≤T0≤323K, and 1.15atm≤P0≤6.2atm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552488A_ABST
    Figure CN119552488A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aerodynamic low-temperature materials, and particularly relates to a low-temperature wind tunnel model surface filling material and a preparation method thereof. The filling material is prepared from the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 10 to 40 parts of carbon fiber powder, 10 to 25 parts of glass fiber powder, 0.5 to 1.5 parts of accelerant and 0.5 to 1 part of curing agent. The surface filling material is smooth in surface, free of cracks and easy to remove, and the applicable M number range is 0.15 < = M < = 4.0; the applicable temperature range is as follows: 77K < = T0 < = 323K; the applicable total pressure range is that P0 is more than or equal to 1.15 atm and less than or equal to 6.2 atm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerodynamic cryogenic technology and specifically relates to a low-temperature wind tunnel model surface filling material and a preparation method thereof. Background Art

[0002] As the cradle of aircraft, wind tunnel is the key to obtaining accurate aerodynamic data. The Reynolds number is an important parameter to measure the simulation capability of wind tunnel. Low-temperature wind tunnel uses low-temperature nitrogen as the medium, supplemented by pressurization and increasing the size of the wind tunnel, which can easily increase the Reynolds number by more than ten times. It is an effective way to achieve high Reynolds number test simulation in engineering.

[0003] In the process of model preparation, various parts are usually connected by screws, which inevitably leave fine gaps and depressions left by screws sinking into the surface. In order not to affect the aerodynamic shape of the model, filling materials (referred to as putty) are needed to fill the gaps and make the surface smooth. Ordinary putty has poor performance at low temperatures and is prone to cracks, bubbles and even falling off, so it is not suitable for low-temperature wind tunnel tests.

[0004] At present, T8 putty is used as putty in low-temperature wind tunnel tests. This putty is very hard after curing, and special tools are needed to remove it. It is easy to damage the model, making it difficult to remove and not conducive to the replacement of model conditions. Therefore, it is necessary to develop a low-temperature putty suitable for low-temperature equipment, with good bonding properties, expansion characteristics, thermal shock resistance, and easy removal at room temperature. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and propose a low-temperature wind tunnel model surface filling material and a preparation method thereof. The surface filling material has a flat surface, no cracks, and is easy to remove. The applicable M number range is: 0.15≤M≤4.0; the applicable temperature range is: 77K≤T0≤323K; the applicable total pressure range is: 1.15atm≤P0≤6.2atm.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A low-temperature wind tunnel model surface filling material comprises the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 10-40 parts of carbon fiber powder, 10-25 parts of glass fiber powder, 0.5-1.5 parts of accelerator, and 0.5-1 part of curing agent.

[0008] As a preferred embodiment of the above scheme, the filling material includes the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 10 parts of carbon fiber powder, 25 parts of glass fiber powder, 0.5 parts of accelerator, and 0.5 parts of curing agent.

[0009] As another preferred embodiment of the above scheme, the filling material includes the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 20 parts of carbon fiber powder, 10 parts of glass fiber powder, 0.5 parts of accelerator, and 0.5 parts of curing agent.

[0010] Preferably, the accelerator is LB-E1 accelerator, which is a general accelerator prepared with cobalt isooctanoate and styrene as main raw materials.

[0011] Preferably, the curing agent is tert-butyl peroxide-2-ethylhexanoate.

[0012] Preferably, the Shore hardness of the filling material is 50-60 degrees.

[0013] The present invention also provides a method for preparing a low-temperature wind tunnel model surface filling material, the preparation method comprising:

[0014] Take 196 unsaturated polyester resin as the base, add carbon fiber powder, glass fiber powder, accelerator and curing agent in sequence, stir and mix evenly at room temperature to obtain the product.

[0015] Preferably, the carbon fiber powder is selected from Toray T700 carbon fiber powder.

[0016] Preferably, the glass fiber powder is 500-700 mesh glass fiber powder.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The filling material of the present invention has good filling performance, and does not crack, collapse, or fall off at high or low temperatures, and the hardness is also greatly reduced. The hardness of the 196 unsaturated polyester resin-based filling material at room temperature is reduced by 37% compared with T8 putty (HD=80), which plays a significant role in improving the removability, and will not cause damage to the model surface after removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a macroscopic picture of 196 unsaturated polyester resin-based filling material;

[0020] Figure 2 This is a scanning electron microscope image of 196 unsaturated polyester resin-based filling material;

[0021] Figure 3 This is a macroscopic photograph of the filling material morphology after being placed at an ambient temperature of 77K for 48 hours;

[0022] Figure 4 This is a macroscopic photograph of the filling material morphology after being placed at an ambient temperature of 110K for 48 hours;

[0023] Figure 5These are macroscopic photos of the filling material morphology after being placed at different ambient temperatures for 48 hours;

[0024] Figure 6 These are macroscopic photos of the filling material morphology before and after it falls;

[0025] Figure 7 It is a macroscopic picture of the appearance after the filling material is polished;

[0026] Figure 8 This is a comparison of the appearance of samples stored for different days;

[0027] Fig. 9 It is the graph of filling material dL / Lo changing with temperature;

[0028] Fig.10 The hardness data of the filling material after being placed at different ambient temperatures for 48 hours and the cleaning effect diagram;

[0029] Fig.11 These are macroscopic photos of the filling material morphology after wind tunnel tests at different M numbers;

[0030] Fig.12 These are macroscopic photographs of the filling material morphology after wind tunnel tests under different total pressures. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0032] Example

[0033] (1) Experimental reagents

[0034] The main experimental reagents used in this experiment are: unsaturated polyester resin, glass fiber, carbon fiber powder, LB-E1 accelerator, tert-butyl peroxide-2-ethylhexanoate (TBPO) curing agent, etc. The reagent specifications and manufacturers are shown in Table 1.

[0035] Table 1 Main experimental reagents

[0036]

[0037] (2) Curing time of filling material samples

[0038] At room temperature, the mixture is prepared according to the ratio of the components, and after being completely mixed, it is placed in a mold and cooled to form. The curing time is shown in Table 2.

[0039] Table 2 Curing time of 196 unsaturated polyester resin

[0040]

[0041]

[0042] The curing time of the sample is related to the amount of accelerator and curing agent used. According to the curing time table, the curing time of Examples 1-6 is sufficient for the operator to evenly apply the filling material to multiple locations on the surface of the model, but when the added amount of the curing agent and accelerator is 0.5g, the curing time is longer and the operability is best.

[0043] (3) Macroscopic characteristics of filling material samples

[0044] The filling mold is a rectangular stainless steel block with a length of 50mm, a width of 10mm and a height of 5mm. There are three blind holes in the stainless steel block. These three blind holes are used to simulate the screw cap holes on the wind tunnel test model. The same group of samples are filled with filling materials at three locations at one time to ensure the repeatability of the test. After the test is completed, the filling material is removed from the mold to simulate the process of removing the sample from the screw cap hole in the wind tunnel test.

[0045] The appearance of the sample of the filling material of the present invention is gray, and the surface of the screw hole is smooth and crack-free after filling. Figure 1 As shown, Figure 1 In the figure, (a) shows a carbon fiber content of 10 parts, (b) shows a carbon fiber content of 25 parts, and (c) shows a carbon fiber content of 35 parts. Figure 1 It can be seen that as the amount of carbon fiber increases, the color of the sample changes from light gray to dark gray.

[0046] (4) Microscopic characteristics of filling material samples

[0047] By observing the surface of the sample through a scanning electron microscope, we can see the microscopic morphology of the sample surface, which will reflect the law of sample solidification. By observing the cross section of the sample through an electron scanning microscope, we can see the fibrous structure, which is the shape of the added fiber magnification. The support of glass fiber and carbon fiber ensures the strength of the experimental sample in a wide range of high / low temperature. Scanning electron microscope images are as follows: Figure 2 shown. Figure 2 In the figure, (a) is a surface view of the filling material sample, and (b) is a cross-sectional view of the filling material sample.

[0048] Figure 2 It can be shown that at a scale of 10μm, the surface of the filling material is wrinkled. This is because during the solidification process, the resin will release heat and produce shrinkage stress during solidification. After magnification, the appearance shows this wrinkled shape, which is a normal exothermic shrinkage phenomenon. At a scale of 200μm, the cross-section of the unsaturated polyester resin with added fibers has many cylindrical strips, and the fiber tissue is crisscrossed in the resin matrix. These cylindrical fiber tissues play a supporting role in the resin matrix.

[0049] (5) Filling material sample performance test

[0050] 1) Hardness test

[0051] Hardness is a basic physical property of a material. The hardness value represents the hardness of the material and the difficulty of removal. This experiment uses a Shore D hardness tester for hardness testing. Through practice, it is known that generally Shore hardness below 60 can be removed manually and is easy to remove. The room temperature hardness results of the samples before high / low temperature testing are shown in Table 3.

[0052] Table 3 Room temperature hardness values ​​of 196 unsaturated polyester resin-based filling material samples Unit: degree

[0053]

[0054] By analyzing the hardness of Examples 1-6, it was found that the filling performance of this series of filling materials was good, and no cracking, collapse, or shedding occurred at high or low temperatures, and the hardness also dropped significantly. The hardness of the 196 unsaturated polyester resin-based filling material at room temperature was reduced by 37% compared with T8 (HD=80), which will significantly improve the removal performance.

[0055] Combined with the above data on curing time and hardness, the formula of Example 2 is the optimal formula, and the samples of Example 2 are used as the main research objects in subsequent testing experiments.

[0056] 2) Applicable temperature test

[0057] By filling the same batch of filling materials into the imitation screw hole mold under different temperature conditions (77K≤T0≤323K) and placing it for different time periods (24h-48h), repeated measurements were carried out. After the temperature assessment test, it was observed that the filling surface remained flat and crack-free after being placed for a long time at different temperatures (such as Figure 3-5 As shown; Figure 3 In the figure, (a) is after removal, and (b) is after defrosting; Figure 4 In the figure, (a) is after removal, and (b) is after defrosting; Figure 5 (a) is at 300K ambient temperature, (b) is at 323K ambient temperature). After 48h of low temperature testing, the macroscopic morphology of the sample did not change significantly, except for a layer of white frost on the surface. This is because the humidity in the air is high, and under a large temperature difference, the water vapor in the air will condense into frost on the mold and sample surface, which does not affect the use of the filling material.

[0058] 3) Adhesion test

[0059] After the sample is polished, two tests are performed to observe whether the sample's adhesion meets the standard: (1) the sample is dropped freely 10 times from a height of 20 cm above the ground to observe whether the sample will fall off the mold; (2) the sample is slammed against the ground 10 times in a row to observe whether the sample will fall off the mold. Figure 6 As shown, (a) is before free fall, and (b) is after free fall 10 times.

[0060] Through the tests of the above two experimental methods, the sample did not fall off the mold, which proves that the sample is tightly bonded to the metal mold and can withstand a certain degree of vibration and impact.

[0061] 4) Polishability test

[0062] Referring to the use of putty in construction and combining with the common sense of construction workers, putty is usually applied thickly, and then scraped and polished to make the surface smooth and flat, to ensure that the aerodynamic characteristics of the equipment surface in the wind tunnel test are not affected. Therefore, in the experiment, the surface of the mold was also thickly coated, scraped flat after half drying, and then the surface of the sample was polished to make it smooth and flat. In this way, the sample polishing speed can be obtained, and thus the strength of the sample's polishing resistance can be obtained. Grinding comparison Figure 7 As shown, (a) is before grinding, (b) is after grinding; Figure 7 It can be seen that the surface filling materials of this series have good polishability, and no cracks or slag appear after polishing. The surface of the filling material is flat and smooth after polishing, and it is tightly bonded to the metal mold interface.

[0063] 5) Stability test

[0064] Considering that in actual engineering applications, samples are usually not used up and need to be stored in a cool place away from light and wind for subsequent use, it is necessary to maintain a certain stability after the sample is opened in the sealed can. The experiment selected the sample of Example 2. No curing agent was added after the preparation was completed, so that the sample could not produce a polymerization reaction. In the experimental simulation construction, the sample was opened and placed in the air for 5 days and 10 days respectively. After the placement time was satisfied, the curing agent was added for curing, and then the hardness, high / low temperature resistance test, adhesion, and removability after curing were tested to see if they still met the standards. The test showed that they all met the standards. The appearance of the sample is as follows Figure 8 As shown, Figure 8 In the figure, (a) is the uncured initial sample, (b) is the sample after 5 days of curing, and (c) is the sample after 10 days of curing. Figure 8 It can be seen that the fluidity of the sample has no obvious change after 5 days of placement, while the fluidity of the sample after 10 days of placement is not as good as the initial sample, and the sample appears dry.

[0065] 6) Thermal shock resistance test

[0066] Considering that the filling material is often affected by the rapid change of ambient temperature during use, in order to determine the ability of the filling material to resist thermal shock, the rapid cooling and heating method was used to test its thermal shock resistance. After the filling material is filled into the mold for curing and polishing, the filled mold is placed in a liquid nitrogen tank (77K) for 30 minutes, and the sample is taken out and then directly placed in a 323K oven for 30 minutes. This is a rapid cooling and heating cycle. After 10 cycles, it was found that the filling material and the metal mold interface were still tightly bonded and no falling off occurred.

[0067] 7) Thermal expansion characteristics test

[0068] Through the electromagnetic induction thermomechanical method, the movement of the ejector pin can be used to transmit the signal to the differential transformer, and after amplification and conversion, the elongation of the sample at different temperatures can be measured, and then its linear expansion coefficient (ΔL / L 0 =a 1 Δt), where: ΔL---sample expansion and contraction, L 0 ---Original sample length, Δt---Time change, a 1 ---Linear expansion coefficient. The thermal expansion coefficient of the filling material on the surface of the model changes with temperature. Fig. 9 As shown, it basically presents a linear change without any mutation, which indicates that its structure after curing is stable in a wide temperature range.

[0069] The filling material is an organic matrix, and the thermal expansion rate will be slightly accelerated when the temperature is above 30°C. Within the measured temperature range, the thermal expansion coefficient of the filling material is (6.19~33.5)×10 -6 / K. According to the literature, the thermal expansion coefficient of metal mold material-steel is (10~20)×10 -6 / K. Comparison of the thermal expansion coefficients of the two shows that the thermal expansion coefficients of the filling material and the metal mold material are basically in the same order of magnitude, and the change trends of the thermal expansion coefficients of the filling material and the metal mold material are also consistent, both increasing with the increase of temperature, which ensures the close bonding between the filling material and the metal mold interface in a wide temperature range and the good thermal shock resistance of the filling material.

[0070] 8) Removability test

[0071] At present, low-temperature equipment uses T8 putty as putty. This putty has a high hardness after curing (HD=80), requires special tools to remove and is easy to damage the model, making it difficult to remove and not conducive to model condition replacement. The room temperature hardness of the sample of the present invention is relatively low (average HD=50.3), which is 37% lower than the room temperature hardness of T8. After the high / low temperature test, the hardness value does not change much, and can be manually removed with conventional tools. It has excellent removability, and the filling material is removed cleanly without adhesion (such as Fig.10 shown). Fig.10 In the figure, (a) shows the hardness data of the filling material after being placed at different ambient temperatures for 48 hours, (b) shows that the filling material can be manually removed using conventional tools after being placed at an ambient temperature of 110K for 48 hours, and (c) shows the removal effect. When the sample after the high / low temperature test is removed using an awl, the sample will crack into powder under the action of external force due to the local concentrated stress, which is easy to remove. However, under uniform stress, the sample is not easy to crack. The experimental samples are mainly used in large-scale wind tunnel tests. The test environment is under uniform stress for a long time and will not crack during use.

[0072] 9) Applicable M number (Mach number) test

[0073] By filling the same batch of filling materials into the screw holes of a certain equipment bracket, multiple tests were carried out under different wind tunnel test conditions (0.15≤M≤4.0) in a 0.3m low-temperature wind tunnel and a 0.6m transonic wind tunnel to observe the surface morphology of the filling materials after the wind tunnel test. Fig.11 As shown, Fig.11 In, (a)M=0.15, (b)M=0.7, (c)M=1.3, (d)M=3, (e)M=4; Fig.11 It is shown that the surface of the filling material is smooth and crack-free at different Mach numbers.

[0074] 10) Applicable total pressure test

[0075] By filling the same batch of filling materials into the screw holes of a certain equipment bracket, multiple tests were carried out under different wind tunnel test conditions (1.15atm≤P0≤6.2atm) in a 0.3m low-temperature wind tunnel and a 0.6m transonic wind tunnel. After the wind tunnel test, it was observed that the surface of the filling material was smooth and crack-free ( Fig.12 ), Fig.12 In the figure, the total pressure in (a) is 1.15 atm, the total pressure in (b) is 3.0 atm, and the total pressure in (c) is 6.2 atm.

[0076] Taking 196 unsaturated polyester resin as the matrix, by optimizing the filler content and curing parameters in the resin, a wide temperature range model surface filling material formula that meets the requirements of engineering applications is obtained. This filling material is suitable for low-temperature equipment and has good bonding properties, expansion characteristics, thermal shock resistance and is easy to remove. Compared with the T8 putty currently used in low-temperature equipment, the room temperature hardness is reduced by 37%. It can be manually removed without special tools and will not damage the model, making it convenient to replace model conditions.

[0077] The technical indicators of the surface filling material of the present invention have been achieved and verified by experiments on wind tunnel equipment: the applicable M number range is 0.15≤M≤4.0, the applicable temperature range is 77K≤T0≤323K, and the applicable total pressure range is 1.15atm≤P0≤6.2atm; after the test, the putty surface is smooth, crack-free, and easy to remove.

[0078] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.

[0079] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.

Claims

1. A low temperature wind tunnel model surface filling material, characterized in that: The filling material comprises the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 10-40 parts of carbon fiber powder, 10-25 parts of glass fiber powder, 0.5-1.5 parts of accelerator, and 0.5-1 part of curing agent.

2. The low-temperature wind tunnel model surface filling material according to claim 1, characterized in that: The filling material includes the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 10 parts of carbon fiber powder, 25 parts of glass fiber powder, 0.5 parts of accelerator, and 0.5 parts of curing agent.

3. The low-temperature wind tunnel model surface filling material according to claim 1, characterized in that: The filling material includes the following components in parts by weight: 100 parts of 196 unsaturated polyester resin, 20 parts of carbon fiber powder, 10 parts of glass fiber powder, 0.5 parts of accelerator, and 0.5 parts of curing agent.

4. The low-temperature wind tunnel model surface filling material according to any one of claims 1 to 3, characterized in that: The accelerator is LB-E1 accelerator.

5. The low-temperature wind tunnel model surface filling material according to any one of claims 1 to 3, characterized in that: The curing agent is tert-butyl peroxide-2-ethylhexanoate.

6. The low-temperature wind tunnel model surface filling material according to any one of claims 1 to 3, characterized in that: The Shore hardness of the filling material is 50-60 degrees.

7. The low-temperature wind tunnel model surface filling material according to any one of claims 1 to 3, characterized in that: Applicable M number range of surface filling materials: 0.15≤M≤4.0; applicable temperature range: 77K≤T0≤323K; applicable total pressure range: 1.15atm≤P0≤6.2atm.

8. A method for preparing a low-temperature wind tunnel model surface filling material, the preparation method comprising: Take 196 unsaturated polyester resin as the base, add carbon fiber powder, glass fiber powder, accelerator and curing agent in sequence, stir and mix evenly at room temperature to obtain the product.

9. The preparation method according to claim 8, characterized in that: The carbon fiber powder is selected from Toray T700 carbon fiber powder.

10. The preparation method according to claim 8, characterized in that: The glass fiber powder is 500-700 mesh glass fiber powder.